Behavioral objectives and instructional materials in elementary social studies - Garces, Felonila P. 1941- (1975)
The purpose of this study is to illustrate how behaviorally stated objectives influence the preparation of instructional materials in elementary social studies.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Social sciences -- Study and teaching